Sourcing practices of manufacturers in the Malaysian electronics and electrical products industry - Md Sidin, Samsinar; Ng, Gek Cheng (Universiti Putra Malaysia Press, 1998)
The main objective of this study was to identify the sourcing practices currently followed in the electrical and electronics products industry in Malaysia. The findings show that the manufacturers rely on local vendors for material inputs for packaging printed material, metal pans and chemicals but not for TV and VCR chassis. The study also found that price, product delivery and quality are three major factors considered in the selection of vendors. The manufacturers are in general more satisfied with non-local vendors, and are quite satisfied with the local vendors' financing terms, maintenance and after-sales service. To be more competitive, it is suggested that local vendors emphasize research and development of their products. Local vendors also need to focus on product quality and consistently maintain good service.